PENERAPAN MODEL PROBLEM BASED LEARNING DISERTAI VIDEO TRACKER MATERI MOMENTUM DAN IMPULS UNTUK MEMBELAJARKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA - Uswatun Hasanah; Albertus Djoko Lesmono; Sri Astutik (FKIP Universitas Jember, 2019)
This study aims to describe the level of critical thinking ability of a high school students in Situbondo after the application of problem based learning model with a tracker video on momentum and impulse materials. The population were all of the 1st grade students in SMAN 1 Suboh Situbondo. The sample determination were using purposive sample technique. The sample used was X MIPA 2 and X MIPA 4 class. The results concluded that after the application of problem based learning model with tracker video, the level of student’s critical thinking abilities is good. From the six critical thinking indicators, namely interpretation, analysis, evaluation, inference, explanation and self regulation, the indicator that has the highest percentage is interpretation with a very good category. While the indicator that has the lowest percentage is inference in the good category.